Watchmen. Chapter 1 [videorecording (Blu-Ray)] - Straczynski, J. Michael, 1954-; Moore, Alan, 1953-; Gibbons, Dave, 1949- (Warner Bros., 2024)
In an alternate world history set in 1985, the murder of a government sponsored superhero draws his outlawed colleagues out of retirement and into a mystery that threatens to upend their personal lives and the world itself.